Study the effect of ionosphere on the received mobile satellite signal using low-power gps receiver - Awai, D. (Universiti Malaysia Sarawak, UNIMAS, 2010)
This project presents a method to analyse the effect of ionosphere on the eceived Mobile Satellite signal using low power Global Positional System (GPS) receiver. The research involves measurement, experimental and analysis data. In this project, a simple, easy and low-cost data acquisition that can be used for experimental and measurement work to stimulate and visualize the mobile satellite signal performance is proposed. The analysis of the signal performance under the normal situation measurement is performed with respect to signal noise ratio (SNR), elevation and azimuth angles. The NMEA Extractor was used to extract the NMEA data using C++ programming language. The graphical presentation is constructed based on the NMEA extractor data using software called Ngraph. Ngraph is used because the software is simple, cheap and analysis can be done easy. The comparison between the normal situation and open space measurement is carried out in order to shown the satellite signal performance.